The Association Normal Weight Central Obesity Hypertension in Adult – A Systematic Review and Meta-analysis - Yuanda Putri Rizki Ramadhani (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Obesity is a major global health concern, traditionally assessed using body mass index (BMI). However, BMI fails to reflect fat distribution, particularly central obesity, which is closely associated with cardiometabolic risks. Individuals with normal BMI but excessive abdominal fat referred to as normal weight central obesity (NWCO) may face increased risk of hypertension, a condition often overlooked due to normal weight status.This study aimed to systematically review and synthesize current evidence on the association between NWCO and the risk of hypertension in adults, with a focus on sex-specific differences. Eligible studies included adult populations (18–65 years), defined NWCO using waist circumference or waist-to-hip ratio, and reported odds ratios for hypertension. Data were pooled using a random-effects model, and heterogeneity was assessed using the I² statistic.The pooled analysis from six cross-sectional studies revealed a significant association between NWCO and hypertension in both sexes, with a higher odds ratio in males (OR = 9.18) than in females (OR = 1.45). Biological mechanisms, including visceral fat activity and hormonal influences, may explain these sex-based differences. Limitations such as heterogeneity, reliance on cross-sectional data, and inconsistent measurement criteria were noted, suggesting the need for caution in interpretation and application. NWCO is significantly associated with increased hypertension risk, particularly among men. These findings call for routine waist-based assessments in clinical practice and further longitudinal research using standardized methods to clarify causality and guide prevention strategies.